2020
DOI: 10.1016/j.pss.2020.104896
|View full text |Cite
|
Sign up to set email alerts
|

Linking studies of tiny meteoroids, zodiacal dust, cometary dust and circumstellar disks

Abstract: Tiny meteoroids entering the Earth's atmosphere and inducing meteor showers have long been thought to originate partly from cometary dust. Together with other dust particles, they form a huge cloud around the Sun, the zodiacal cloud. From our previous studies of the zodiacal light, as well as other independent methods (dynamical studies, infrared observations, data related to Earth's environment), it is now established that a significant fraction of dust particles entering the Earth's atmosphere comes from Jup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Besides, observations of debris disks have now shown that light scattering properties of dust in debris disks are far from those predicted by Mie theory and in favour of irregular dust particles, as pointed out essentially by phase functions analysis [19][20]. These results can greatly benefit from in situ and remote cometary observations and from advanced modelling of cometary dust, and at the same time provide examples of dust properties in other stellar systems to put our own Solar System into context [1].…”
Section: Significance Of the Results Back In Time And Beyond In Spacementioning
confidence: 98%
See 1 more Smart Citation
“…Besides, observations of debris disks have now shown that light scattering properties of dust in debris disks are far from those predicted by Mie theory and in favour of irregular dust particles, as pointed out essentially by phase functions analysis [19][20]. These results can greatly benefit from in situ and remote cometary observations and from advanced modelling of cometary dust, and at the same time provide examples of dust properties in other stellar systems to put our own Solar System into context [1].…”
Section: Significance Of the Results Back In Time And Beyond In Spacementioning
confidence: 98%
“…The interpretation of polarimetric observations, at given phase angles and wavelengths, is a powerful tool to better understand the composition and physical properties of these irregular dust particles and their formation processes. It now provides clues to the origin of the Solar System and to some characteristics of dust in stellar systems, as discussed in [1].…”
Section: Discussionmentioning
confidence: 98%
“…Continued monitoring of the zodiacal light over time will provide a better understanding of the origin and evolution of the interplanetary dust environment. Going one step further, the study of the similarities between the light scattering behavior of interplanetary dust particles, asteroids, cometary dust clouds and protoplanetary disks will help us understand planetary formation processes and the origin of the solid particles in these different environments (Levasseur-Regourd et al, 2020).…”
Section: Properties Of Interplanetary Dust and Their Link With Cometsmentioning
confidence: 99%
“…Jenniskens et al (2008) reported a lack of fluffy meteoroid in an old Leonid trail, which these authors suggested is possibly explained by meteoroid self-disruption in the interplanetary space (although, other hypotheses might explain this observation). In order to explain the present quasi-steady-state of the level of sporadic meteors and of the amount of zodiacal dust, models must take the meteoroid life expectancy into account as well as the replenishment mechanism (Wiegert et al 2009;Levasseur-Regourd et al 2020). Such mechanisms include the gravitational perturbation of long-period comets, the structure and population of the Oort cloud, the role of giant planets (especially Jupiter) in removing or accreting small bodies in the inner Solar System, and so on.…”
Section: Introductionmentioning
confidence: 99%